PERLINDUNGAN HAK ASASI MANUSIA BAGI PENGUNGSI DI NEGARA NON-ANGGOTA KONVENSI STATUS PENGUNGSI 1951 [Human Rights Protection for Refugees in Non-Member Countries of the 1951 Refugee Status Convention] - Fransiska Ayulistya Susanto (Law Review, 2020)
Refugee problems become global problems not only for destination country but also for the transit or non-parties country on Status of Refugees Convention 1951. The problem arises when the transit or non-parties country ignore the existence of the refugees in their territory consequently, many refugees could only depend on their protection under UNHCR help. Even if, the territorial state is not the party of 1951 convention, however, they still have responsibility under another Human Rights Convention to give protection to the refugees. Therefore, how far the refugees shall be protected under the transit territory? This article will have analyzed minimum protection under Human Rights instruments and Customary International Law that could give to the refugees. Under the International Covenant on Civil and political Rights, International Covenant on Economic, Social and Cultural Rights, International Convention on The Rights of the Child and Customary International Law, the state territory shall give protection without any discrimination to the refugees, even if they are not the party of 1951 convention. Even though, the protection that refugees get from transit state slightly different than protection from state parties, however, they shall get to be protected.Bahasa Indonesia Abstrak: Masalah pengungsi sudah menjadi permasalahan global yang tidak hanya berpengaruh terhadap negara tujuan saja, namun juga pada negara transit atau negara yang bukan merupakan negara anggota Konvensi Status Pengungsi 1951. Masalah timbul saat negara-negara transit atau negara non-anggota mengabaikan keberadaan pengungsi di teritori negara mereka, sehingga banyak pengungsi yang hanya menyandarkan nasibnya di tangan bantuan UNHCR. Meskipun negara teritorial bukan merupakan negara anggota Konvensi Status Pengungsi 1951, namun mereka seharusnya tetap memberikan perlindungan kepada pengungsi. Pertanyaannya, seberapa jauh negara harus memberikan perlindungan kepada pengungsi? Artikel ini akan menganalisis perlindungan minimal di bawah Hak Asasi Manusia yang harus diberikan negara non-anggota kepada pengungsi yang ada di wilayahnya. Menurut Konvenan tentang Hak-Hak Sipil dan Politik, Konvenan Hak-Hak Ekonomi, Sosial dan Budaya, serta Konvensi Perlindungan Anak dan juga hukum kebiasaan internasional, negara teritorial haruslah memberikan perlindungan tanpa diskriminasi kepada pengungsi, meskipun negara teritorial tidak menjadi para pihak dari Konvensi Status Pengungsi 1951. Meskipun perlindungan yang diberikan kepada pengungsi oleh negara transit sedikit berbeda jika dibandingkan perlindungan dari negara anggota konvensi, mereka tetap harus mendapatkan perlindungan.